2022
DOI: 10.1021/acs.chemmater.1c03971
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the Ionic Conductivity of Poly(3,4-propylenedioxythiophenes) with Oligoether Side Chains for Use as Conductive Cathode Binders in Lithium-Ion Batteries

Abstract: Mixed electron- and ion-conducting polymers serve as excellent candidates for polymer binders in lithium-ion batteries (LIBs) because of an extension of functionality beyond simple mechanical adhesion. Such dual conduction was observed in our recent report on dihexyl-substituted poly­(3,4-propylenedioxythiophene) (PProDOT-Hx2), which showed excellent performance as a cathode binder for LiNi0.8Co0.15Al0.05O2 (NCA). However, ionic conductivity was found to be significantly lower than that of its electronic count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(84 citation statements)
references
References 92 publications
2
81
0
Order By: Relevance
“…These measurements indicate that EG side chains significantly increase Li-ion diffusion and result in electrodes with mixed ionic and electron transport. This is consistent with recent reports that studied simultaneous ionic and electronic transport in different conjugated polymers, including conjugated polymers with oligoether side chains . These studies measured electronic and ionic conductivities simultaneously as a function of potential and demonstrated that oligoether side chains enhanced ionic conductivity while reducing electronic conductivity …”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…These measurements indicate that EG side chains significantly increase Li-ion diffusion and result in electrodes with mixed ionic and electron transport. This is consistent with recent reports that studied simultaneous ionic and electronic transport in different conjugated polymers, including conjugated polymers with oligoether side chains . These studies measured electronic and ionic conductivities simultaneously as a function of potential and demonstrated that oligoether side chains enhanced ionic conductivity while reducing electronic conductivity …”
Section: Resultssupporting
confidence: 92%
“…This is consistent with recent reports that studied simultaneous ionic and electronic transport in different conjugated polymers, 34 including conjugated polymers with oligoether side chains. 35 These studies measured electronic and ionic conductivities simultaneously as a function of potential and demonstrated that oligoether side chains enhanced ionic conductivity while reducing electronic conductivity. 35 We were also interested in measuring the electronic conductivity of the PNDI-EG materials.…”
Section: ■ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of specific interest in recent literature is using MIECs as protective coatings and binders for Li-ion battery electrodes. PVDF, the most widely used polymer binder, suffers from low electronic and Li-ion conductivities. This increases electrode impedance by interfering with charge transport during battery operation. It stands to reason that utilizing a polymeric MIEC would lower this impedance and improve battery performance.…”
Section: Introductionmentioning
confidence: 99%
“…With the help of the significance of ME@AM and its strong ties to the binder system, we can comprehensively summarize the past efforts, the challenges, and future opportunities for the studies of binders. In general, the past efforts on binder research can be divided into three categories: improvement of adhesion or component binding capability, [18][19][20][21][22][23][24][25] functionalization for ion/electron conduction or volume change accommodation, [16,17,23,[26][27][28][29][30][31] and the rational design of binder systems for electrode processing innovation as well as microstructure management. [2,[32][33][34][35] Specifically, to improve the adhesion property that is critical for stabilizing the structures/interfaces of ME@AM, lots of efforts can be found on replacing poly(vinylidene fluoride) (PVDF) by other polymers with abundant polar functional groups (e.g., COOH, CN, OH, etc.).…”
Section: Introductionmentioning
confidence: 99%